A New Contemporary Model of Brand Fidelity: A Sustainable Clothing Brand Perspective - Elisa Veliana Putranto Walujo; Michael Adiwijaya; Halimin Herjanto (Indonesian Journal of Sustainability Accounting and Management, 2023)
The concept of brand is notoriously difficult to define and the findings of existing studies on this concept are mixed and inconclusive. This current study enriches the brand study reservoir by developing a new conceptual model of brand fidelity. It also presents a set of hypotheses that aim to provide a better understanding of the moderating effect of brand prominence and self-brand connection on the relationship between brand love and brand fidelity. The responses of 200 Indonesian online respondents were analyzed using Smart-PLS. The statistical results demonstrate that brand love, brand prominence, and self-brand connection positively and significantly influence brand fidelity. In contrast, it was found that brand prominence does not moderate the relationship between brand love and brand fidelity, while self-brand connection negatively and significantly does. Further, this study provides future research avenues and important implications for academics and business practitioners.